2012
DOI: 10.1590/s0100-204x2012001000004
|View full text |Cite
|
Sign up to set email alerts
|

Ácido cianídrico em tecidos de mandioca em função da idade da planta e adubação nitrogenada

Abstract: Resumo -O objetivo deste trabalho foi avaliar o teor de ácido cianídrico em tecidos de mandioca, em função da idade da planta e níveis de adubação nitrogenada. Utilizou-se o delineamento experimental de blocos ao acaso, em arranjo de parcelas subdivididas, com quatro repetições. As doses de nitrogênio em cobertura (0, 30, 60, 150 e 330 kg ha -1 ) foram alocadas nas parcelas, e as épocas de avaliação (90, 120, 150, 180, 240, 300 e 360 dias após o plantio), nas subparcelas. Os teores de ácido cianídrico foram av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
5
0
4
Order By: Relevance
“…In a study conducted by Oliveira et al (2012) it was concluded that the hydrocyanic acid (HCN) content in the 'Aciolina' cultivar had a positive response to increased doses of topdress N (30, 60, 150, and 330 kg ha -1 ). The synthesis of plant secondary compounds is more influenced by agricultural practices (fertilizers, application of manure, and burning of crop residues) than by seasonal factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Oliveira et al (2012) it was concluded that the hydrocyanic acid (HCN) content in the 'Aciolina' cultivar had a positive response to increased doses of topdress N (30, 60, 150, and 330 kg ha -1 ). The synthesis of plant secondary compounds is more influenced by agricultural practices (fertilizers, application of manure, and burning of crop residues) than by seasonal factors.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that can influence the concentration of glycosides among cultivars, among them, genetic, environmental, soil type, location, time of year, which may result in the concentration of up to 2000 mg kg -1 in tubers, as well as in leaves. Oliveira et al (2012), highlight that nitrogen fertilization and harvest time can influence the HCN content in plant parts. When N doses were between 219 and 241 kg ha -1 , there were higher accumulations of HCN (401 mg kg -1 ) in the cortex, and lower accumulation (332 mg kg -1 ) in the root pulp.…”
Section: Relevant Aspects Of Cassava Culturementioning
confidence: 99%
“…Fertilizers application in cassava cultivation proved to be another factor limiting the production. When analyzing different levels of [17] observed there is a direct relationship between applied dosages with root production and length. Experiments performed by [18] corroboraterelation between macronutrientdosages with the increase of root diameter.…”
Section: Fertilization Managementmentioning
confidence: 99%